Pengaruh Integrasi Bahan Ajar Media Picture Series Berbasis Flash Melalui Pendekatan Komunikatif Terhadap Kemampuan Bercerita - Ndapa Lawa, Selfiana Triyanty. M. (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The purpose of this study was to know a significant influence of integrated flash picture series media through communicative approach towards storytelling ability. The research method used quasi-experimental design with nonequivalent control group and saturated sampling technique and a sample size of 20 students.The reasearch instrument used test questions and documentation studies, while the data analysis used independent t-test and effect size test. The result showed an increase in student learning outcomes with the use of flash-based pictured series through communicative approach and it showed group of students who were taught effectively with flash-based media with an average value of 56.45 at pre-test to 81.55 in post test compared to the control group which was valued only 51.95 at pre-test increased to 62.9 after the post test. The research showed the use of flash-based picture media through communicative approach was effective in teaching 7th grade students of SMP Negeri 3 Kupang on English subject especially speaking material (storytelling). The result was proved by Ha > Ho r 81.55 > 62.9.